Field Building Leadership Initiative (FBLI): Advancing ecohealth in Southeast Asia - Hung Nguyen-Viet; Adisasmito, W.; Kittayapong, P.; Jing, F.; Xuan Tung Dinh; Phuc Pham Duc (International Livestock Research Institute, 2016)
In response to global environmental health challenges, multi-disciplinary research and training are becoming popular among several countries in the world. However, systemic degree training programmes emphasizing integration of multi-disciplines are still not existed in the Asian Region. With approval from the University Council of Mahidol University, the Degree Programmes in "One Health and Ecosystem Management" are currently under development in collaboration with the University of Indonesia, Kunming Medical University and Hanoi School of Public Health. This will be one big step in integrating One Health/Ecohealth concept and system thinking into university curricula. The main objective is to produce high quality and competent graduates, who have background in multi-disciplinary research aiming at healthy environment and healthy living, to work in either government or private sectors. The research-based topics will be emphasized on an application of One Health/Ecohealth approach to human and animal health, environmental health, emerging and re-emerging infectious diseases, and social science, economics and policy in One Health/Ecohealth. It is expected that the students resulting from these programmes should help bringing One Health/Ecohealth practice into their professional work which hopefully will improve disease management and, hence, improve well-being in the long-term.